Sistem Informasi Pengajuan Dana Hibah Internal Politeknik Kampar Berbasis Website Menggunakan Framework Laravel Vue.Js - Andri Nofiar; Fina Nasari; Diki Wahyudy (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
Currently, internally funded research and community service activities are still carried out at a semi-computerized level, so the data is not yet well integrated. The process of submitting proposals and reporting research activities and community service still uses Google Form, while assessments are carried out using Microsoft Excel. In this process, several obstacles have been identified, one of which is the potential impact of changes to submission data which could affect other data. Therefore, a fully computerized information system will be created, aimed at making it easier for P3M units to manage the internal grant application, assessment and reporting process through an online-based website. The results of this research, the internal grant application system for processing internal grant data has been integrated with the results of black box testing, obtaining a percentage of 100% which is in accordance with the goals and functions of the system. Apart from that, user response testing or User Acceptance Testing (UAT) has been carried out with an average percentage result of 90.83% stating that the system helps in improving the smoothness of the internal grant application process